2015
DOI: 10.1248/bpb.b15-00227
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcemia Leads to Delayed Corneal Wound Healing in Ovariectomized Rats

Abstract: Hypercalcemia is often observed in postmenopausal women as well as in patients with primary hyperparathyroidism or malignant tumors. In this study, we investigated the relationship between calcium ion (Ca 2 ) levels in lacrimal fluid and the rate of corneal wound healing in hypercalcemia using ovariectomized (OVX) rat debrided corneal epithelium. We also determined the effects of Ca 2 levels on cell adhesion, proliferation and viability in a human cornea epithelial cell line (HCE-T). The calcium content in bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…This decrease may be caused by other hormones that regulate Ca 2+ levels in the body, such as calcitonin and parathyroid hormone, and these changes in the biological characteristics correspond to those seen in postmenopausal women. These results are similar to previous reports using OVX rats, 21) and show that the OVX rats used in this study were suitable for investigating changes in Ca 2+ levels and IL-18 expression in lenses after menopause.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This decrease may be caused by other hormones that regulate Ca 2+ levels in the body, such as calcitonin and parathyroid hormone, and these changes in the biological characteristics correspond to those seen in postmenopausal women. These results are similar to previous reports using OVX rats, 21) and show that the OVX rats used in this study were suitable for investigating changes in Ca 2+ levels and IL-18 expression in lenses after menopause.…”
Section: Resultssupporting
confidence: 92%
“…The OVX rat is an accepted female animal model to mimic postmenopausal women. 21,23) The OVX procedure promotes bone loss. Following bilateral ovariectomy, serum Ca 2+ levels rise and bone mass decreases due to the loss of estrogen.…”
mentioning
confidence: 99%
“…The abrasion of the corneal epithelium in the normal and STZ rats was performed as described previously [ 41 , 55 , 70 , 71 , 72 , 73 ]. The rats were anesthetized with sodium pentobarbital (30 mg/kg, i.p.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, previous studies have revealed that an increased intracellular Ca 2+ concentration inhibits epithelial proliferation and promotes epidermal-like differentiation in the mouse cornea [8,10]. Furthermore, hypercalcemia appears to retard corneal wound healing in ovariectomized rats, while, using human corneal epithelial cells, an enhanced intracellular Ca 2+ level results in a decrease in cell viability [11]. These findings are consistent with the clinical observation that chelation of Ca 2+ by the topical application of ethylene-diamine-tetra-acetic acid (EDTA) is an effective way of treating band keratopathy [12,13].…”
Section: Introductionmentioning
confidence: 98%